2011
DOI: 10.1111/j.1756-185x.2011.01630.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in systemic lupus erythematosus and rheumatoid arthritis patients: relationship to disease manifestations and activity

Abstract: Aim: The present work was undertaken to study the status and contribution of oxidative stress in systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) patients. Relationship of the markers of oxidative stress to clinical manifestations, disease activity, damage and medications used were well considered.Methods: Thirty SLE and 30 RA female patients were included in the study and clinical examination and investigations were performed and disease activity was assessed. Markers of oxidative stress, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
101
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(109 citation statements)
references
References 49 publications
5
101
1
2
Order By: Relevance
“…In fact elevated MDA levels and reduced TAS levels also point towards a state of oxidative stress. Shah et al [9] have recently reported inflammatory response in SLE which aggravates oxidative stress with potential to provoke damage to lipids, proteins and DNA [12,13]. The observations of the present study on significantly increased genomic damage also find reflections in the results documented by Montalvao et al [13] who reported 1.3x significantly increased (p=0.000) DNA damage index in 25 SLE patients compared to the value in equal number of healthy controls.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In fact elevated MDA levels and reduced TAS levels also point towards a state of oxidative stress. Shah et al [9] have recently reported inflammatory response in SLE which aggravates oxidative stress with potential to provoke damage to lipids, proteins and DNA [12,13]. The observations of the present study on significantly increased genomic damage also find reflections in the results documented by Montalvao et al [13] who reported 1.3x significantly increased (p=0.000) DNA damage index in 25 SLE patients compared to the value in equal number of healthy controls.…”
Section: Discussionsupporting
confidence: 80%
“…The inflammatory response in SLE exacerbates oxidative stress [9] which tends to promote cellular macromolecular damage, lipid peroxidation and protein oxidation [10,11] and damage to DNA [12,13]. Health can further be compromised as any unrepaired DNA damage can initiate neoplasia [14].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, increasing evidence indicates that nitric oxide is a key regulator of apoptosis in RA [40]. Oxidative stress was reported to be increased and more profound in RA than SLE and could well reflect disease activity [11]. Increased nitric oxide levels have also been observed in HT patients [10].…”
Section: Discussionmentioning
confidence: 90%
“…Markers of oxidative stress are well correlated with disease activity in both SLE and RA [11]. NOS inhibition was reported to decrease the disease activity in experimental RA [12].…”
Section: Introductionmentioning
confidence: 99%
“…Microbiota might have different mechanisms of action over the host balancing anti-and pro-inflammatory responses (10). In line with this, even though it is not clear if oxidative stress is a cause or a consequence of this pathology; recent studies have reported higher levels of the lipid peroxidation subproduct, malondialdehyde (MDA), in lupus patients (11)(12)(13)(14). As both, oxidative stress and inflammation, may be implicated in SLE pathogenesis, they may be affected by the intake of oxidants and antioxidants and the antioxidant capacity from serum (15).…”
Section: Introductionmentioning
confidence: 76%